Muses’ words (Hes. Theog. 22-35) - Rodríguez Alfageme, Ignacio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2017)
Commentary of verses 22-35 of the Theogony focused on interpretation and function of the insults which pronounced the Muses and the delivery of the sceptre as a symbol of the transformation of the pastor in poet.
Keywords: Hesiod; inspiration; insults; sceptre.